2015
DOI: 10.1073/pnas.1505956112
|View full text |Cite
|
Sign up to set email alerts
|

Dengue virus infection elicits highly polarized CX3CR1+cytotoxic CD4+T cells associated with protective immunity

Abstract: Dengue virus (DENV) is a rapidly spreading pathogen with unusual pathogenesis, and correlates of protection from severe dengue disease and vaccine efficacy have not yet been established. Although DENV-specific CD8 + T-cell responses have been extensively studied, the breadth and specificity of CD4 + T-cell responses remains to be defined. Here we define HLA-restricted CD4 + T-cell epitopes resulting from natural infection with dengue virus in a hyperepidemic setting. Ex vivo flow-cytometric analysis of DENVspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
308
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 266 publications
(332 citation statements)
references
References 52 publications
22
308
2
Order By: Relevance
“…Interestingly, although at low level (~0.8%), CD107a expression was also detected in CD4 + T cells. DENV-specific CD4 + CTLs were previously described and shown to lyse target cells (18,21,76) but the low frequency of such cells in the current study suggests a minor role in protection. A large fraction (~19%) of CD8 + T cells in the vaccinated-challenged group also expressed IFN-γ.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…Interestingly, although at low level (~0.8%), CD107a expression was also detected in CD4 + T cells. DENV-specific CD4 + CTLs were previously described and shown to lyse target cells (18,21,76) but the low frequency of such cells in the current study suggests a minor role in protection. A large fraction (~19%) of CD8 + T cells in the vaccinated-challenged group also expressed IFN-γ.…”
Section: Discussioncontrasting
confidence: 51%
“…+ subset, was recently demonstrated in mice (17,18,20) and humans (19,21). To test this hypothesis, 3-wko pups born to DENV-naive or PDK53-immunized dams were vaccinated, or not, with PDK53 and subsequently challenged with D2Y98P-PP1 at 6 weeks of age (20 days after vaccination).…”
Section: Pdk53 Vaccination Protected Against D2y98p-pp1 In the Contexmentioning
confidence: 99%
See 1 more Smart Citation
“…The interplay between low titers, cross-reactive neutralizing antibody titers, and cell-mediated immunity in subjects who are protected is currently unknown. In previous studies, we further showed that either a monovalent or tetravalent DLAV formulation elicited vigorous CD8 ϩ responses comparable to those observed in areas of hyperendemicity and associated with high frequencies of secondary infections and natural immunity (16). However, it is unknown whether tetravalent DLAV vaccination results in the induction of effective CD4 ϩ responses.…”
mentioning
confidence: 85%
“…In animal models of DENV disease, depletion of CD4 ϩ T cells does not exacerbate disease, but their induction with DENV-specific T cell epitopes can protect animals from DENV challenge (15). In humans, DENV-specific CD4 ϩ T cells display unique phenotypes, and in several cases, MHC class II alleles associated with the most vigorous responses are also associated with decreased disease susceptibility (16). These CD4 ϩ T cells dominantly recognize the capsid (C) and the nonstructural 3 (NS3) and NS5 antigens, while the envelope (E) protein appears to be a minor target (17,18).…”
mentioning
confidence: 99%